Antibacterial Properties of Medicinal Plants From Pakistan Against Multidrug-Resistant ESKAPE Pathogens - Khan, Muhammad Faraz; Tang, Huaqiao; Lyles, James T.; Pineau, Rozenn; Mashwani, Zia-ur-Rahman; Quave, Cassandra L. (Frontiers in Pharmacology, 2018)
In the Sudhnoti district of Pakistan, local people share a rich practice of traditional medicine for the treatment of a variety of ailments. We selected nine plants from the Sudhnoti ethnopharmacological tradition used for the treatment of infectious and inflammatory disease. Our aim was to evaluate the in vitro anti-infective potential of extracts from these species against multidrug-resistant (MDR) ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, and Enterobacter species) pathogens. Plant specimens were collected in the Sudhnoti district of Pakistan and vouchers were deposited in Pakistan and the USA. Dried bulk specimens were ground into a fine powder and extracted by aqueous decoction and maceration in ethanol. Extracts were assessed for growth inhibitory activity against ESKAPE pathogens and biofilm and quorum sensing activity was assessed in Staphylococcus aureus. Cytotoxicity to human cells was assessed via a lactate dehydrogenase assay of treated human keratinocytes (HaCaTs). Four ethanolic extracts (Zanthoxylum armatum, Adiantum capillus-venaris, Artemisia absinthium and Martynia annua) inhibited the growth of MDR strains of ESKAPE pathogens (IC50: 256 µg mL-1). All extracts, with the exception of Pyrus pashia and M. annua, exhibited significant quorum quenching in S. aureus agr I. The ethanolic extract of Z. armatum fruits (Extract 1290) inhibited quorum sensing (IC50 32-256 µg mL-1) in S. aureus reporter strains for agr I-III. The quorum quenching activity of extract 1290 was further validated by detection of δ-toxin in the bacterial supernatant, with concentrations of 64-256 µg mL-1 sufficient to yield a significant drop in δ-toxin production. None of the extracts inhibited S. aureus biofilm formation at sub-inhibitory concentrations for growth. All extracts were well tolerated by human keratinocytes (LD50 ≥ 256 µg mL-1). Chemical analysis of extract 1290 by liquid chromatography-Fourier transform mass spectrometry (LC-FTMS) revealed the presence of 29 compounds, including eight with putative structural matches. In conclusion, five out of the nine selected anti-infective medicinal plants exhibited growth inhibitory activity against at least one MDR ESKAPE pathogen at concentrations not harmful to human keratinocytes. Furthermore, Z. armatum was identified as a source of quorum quenching natural products and further bioassay-guided fractionation of this species